Respuesta :
Answer and Step-by-step explanation:
[tex]\Huge\boxed{B=-3}[/tex]
Step 1 : Simplify both sides of the equation :
[tex]-8(8+4b)=20-4b[/tex]
[tex](-8)(8)+(-8)(4b)=20+-4b[/tex] (By Distributing)
[tex]-64+-32b=20+-4b[/tex]
[tex]-32b-64=-4b+20[/tex]
Step 2 : Add [tex]4b[/tex] to both sides :
[tex]-32b-64+4b=-4b+20+4b[/tex]
[tex]-28b-64=20[/tex]
Step 3 : Add [tex]64[/tex] to both sides :
[tex]-28b-64+64=20+64[/tex]
[tex]-28b=84[/tex]
Step 4 : Divide both sides by [tex]-28[/tex] :
[tex]\frac{-28b}{-28}=\frac{84}{-28}[/tex]
[tex]b=-3[/tex]
That should be you're final answer!